IDENTIFIKASI MOTIVASI DAN DUKUNGAN YANG DIPERLUKAN MAHASISWA RETAKER UJI KOMPETENSI MAHASISWA PROGRAM PROFESI DOKTER - Romadhoni romadhoni; Gandes Retno Rahayu; Umatul Khoiriyah (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
Background: Medical students who experience failure in the final exam are around 10%. In Indonesia, there are students who failed to pass the competency test for medical profession program students (UKMPPD) until 14 times. The impact of this failure is the occurence of mental health disorder. Students need support more than guidance on clinical knowledge and skills. This study aimed to identify the motivation and support needed by the UKMPPD retaker students in the effort to achieve graduation Methods: This research is a qualitative research with phenomenological approach, the data was obtained by in-depth interview and focus group discussion (FGD). This research was followed by 16 respondents. The data analysis was conducted by thematic analysis method. Results: Identified intrinsic motivation predictor originated from learning independence, relation, and low competence. The extrinsic motivation predictors are originated from external regulation, that is UKMPPD regulation. The motivation predictor is originated from anxiety and study period limit. The support needed by the respondents from medical schools are in the form of psychological approach, absolving the retaker students from selection tests, providing form of selection tests that compatible with the blueprint and rules of UKMPPD multiple choice question, also giving the opportunity to pass with other exam methods. Conditions of motivation can change with the factors that influence it. Changes in motivational conditions that may occur are an increase in motivational conditions, decreased motivational conditions, or persistent motivational conditions. Conclusion: The motivation condition of retaker students is amotivated and motivated (external and internal motivation). Support from medical school that can increase motivation is given to students to keep their motivation level.